INFORMATION SECURITY STAGES OF THE INTEGRATION OF ALTERNATIVE ENERGY SOURCES IN THE GENERAL ELECTRICAL NETWORK - Davronov, S.R. (SCIENCE and SOCIETY, 2019)
The concept of intelligent networks appeared relatively recently and managed to cover the whole world. The energy infrastructure of developing countries needed to be updated in this direction. But the integration of intelligent electrical networks of this magnitude necessarily requires ensuring information security at a high level. In this work we discuss international standards in information security for the implementation and security of an integrated network.